2020
DOI: 10.3390/ijms21176413
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Addiction, Gut Microbiota, and Alcoholism Treatment: A Review

Abstract: Alcohol addiction is a leading risk factor for personal death and disability. In 2016, alcohol use caused 2.2% of female deaths and 6.8% of male deaths, and disability-adjusted life years (DALYs) were 2.3% in female and 8.9% in male. Individuals with alcohol use disorder are at high risk of anxiety, depression, impaired cognition performance, and illicit drug use and are comorbid with liver disease, such as alcoholic hepatitis and liver cirrhosis, which is a major cause of personal death and disability worldwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 49 publications
(54 reference statements)
0
70
0
5
Order By: Relevance
“…Presently, there are few FDA-approved pharmacological treatments for AUD. These include disulfiram, acamprosate, and naltrexone and these medications have limited success at reducing the high rates of relapse and are not necessarily efficacious in some populations [ 66 , 67 ]. Thus, there is a need to develop other pharmacological agents based on the elucidation of neurobiological mechanisms that might be the substrates of AUD.…”
Section: Potassium Channels and Alcohol Use Disordermentioning
confidence: 99%
“…Presently, there are few FDA-approved pharmacological treatments for AUD. These include disulfiram, acamprosate, and naltrexone and these medications have limited success at reducing the high rates of relapse and are not necessarily efficacious in some populations [ 66 , 67 ]. Thus, there is a need to develop other pharmacological agents based on the elucidation of neurobiological mechanisms that might be the substrates of AUD.…”
Section: Potassium Channels and Alcohol Use Disordermentioning
confidence: 99%
“…And gut microbiota may change the immune state of bone, thus affecting the generation of osteoclasts, but its immune regulation ability of the body will gradually weaken as the age increases (Ticinesi et al, 2019). Moreover, it has been found that alcohol can cause changes to the gut microbiota composition and is closely related to personal health (Wang et al, 2020). However, the relationship between AOP and gut microbiota in different ages was not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, alcohol consumption has been associated with dysbiotic changes in gut microbiome, breakdown of the intestinal barrier integrity and increased permeability of the intestinal mucosa [ 25 , 26 ]. One important source of brain damage and neurodegeneration caused by alcohol use is neuroinflammation [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%